2018
DOI: 10.1016/j.jcyt.2018.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal administration of autologous mesenchymal stromal cells for spinal cord injury: Safety and efficacy of the 100/3 guideline

Abstract: The present guideline for cell therapy is safe and shows efficacy in patients with SCI, mainly in recovery of sphincter dysfunction, neuropathic pain and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 23 publications
0
60
0
1
Order By: Relevance
“…A dosage of 2 × 10 6 cells/kg body weight is commonly given to the patients [6,7]. For certain patients and diseases, multiple administrations of MSCs up to several hundred million cells are needed to achieve the desired therapeutic effect [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A dosage of 2 × 10 6 cells/kg body weight is commonly given to the patients [6,7]. For certain patients and diseases, multiple administrations of MSCs up to several hundred million cells are needed to achieve the desired therapeutic effect [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Variable pattern of recovery in Barthel Index. No significant changes in SEP, MEP and NCV [ 47 ] Chronic A, B, C and D 11 BM Intrathecal 3 × 10 8 BMSCs 3 (every 3 months) No AE Improvement in ASIA pin prick score, ASIA light touch score, ASIA motor score, IANR-SCIFRS score, VAS score and bladder function [ 48 ] Chronic A 14 BM Intraspinal 5 × 10 6 BMSCs/cm 3 lesion volume 1 No AE 7/12 patients showed improvement in AIS grade [ 49 ] Chronic A 40 BM Intraspinal 2 × 10 7 BMSCs 1 No AE 9/20 patients showed improvement in AIS grade from A to B [ 50 ] Chronic A, B and C 20 BM Intraspinal 1 × 10 8 BMSCs 1 No AE 4/8 (50%), 3/4 (75%) and 8/8 (100%) patients with AIS grade A, B and C respectively showed improvement in AIS grade [ 51 ] Subacute and chronic A, B and C 20 BM Intra-arterial and intravenous 104 ± 44.3 × 10 8 BMMCs 1 No AE Improvement in ASIA score in patient...…”
Section: Mesenchymal Stem Cell Therapy For Spinal Cord Injurymentioning
confidence: 99%
“…Besides, there were also no significant changes in SEP, motor evoked potentials (MEP) and nerve conduction velocity (NCV) as well as a variable pattern of recovery in Barthel Index. Vaquero et al [ 47 ] reported improvement in sensation, motor and bladder function, and IANR-SCIFRS score as well as a reduction in neuropathic pain in the chronic SCI patients (time of injury to participation 13.65 ± 14.79 years) received the BMSC therapy.…”
Section: Mesenchymal Stem Cell Therapy For Spinal Cord Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs have proven to be safe or exhibited clinical efficacy in the field of regenerative medicine. Examples include improving neurologic function in amyotrophic lateral sclerosis ( Petrou et al, 2016 ; Sykova et al, 2017 ; Berry et al, 2019 ), cerebral palsy ( Wang X. et al, 2013 ; Huang et al, 2018 ), delayed encephalopathy after carbon monoxide poisoning ( Wang H. et al, 2016 ), epilepsy ( Hlebokazov et al, 2017 ), stroke ( Bang et al, 2005 ; Lee et al, 2010 ), metachromatic leukodystrophy ( Koc et al, 2002 ), and spinal cord injury ( Vaquero et al, 2018 ); improved sexual function in erectile dysfunction ( Al Demour et al, 2018 ); improved motor activity with frailty disorder ( Tompkins et al, 2017 ), and multiple system atrophy ( Lee et al, 2008 , 2012 ; Singer et al, 2019 ); improved cardiovascular function in heart failure ( Hare et al, 2012 ; Golpanian et al, 2015 ; Mathiasen et al, 2015 ; Bartolucci et al, 2017 ), and myocardial ischemia/angina ( Hare et al, 2009 ; Friis et al, 2011 ; Haack-Sorensen et al, 2013 ; Karantalis et al, 2014 ; Kim et al, 2018 ), improved bone repair in hypophosphatasia ( Taketani et al, 2015 ), lumbar disc degeneration ( Orozco et al, 2011 ; Noriega et al, 2017 ), osteogenesis imperfecta ( Gotherstrom et al, 2014 ), and osteonecrosis ( Hernigou et al, 2018 ); improved healing from kidney injury ( Tan et al, 2012 ; Saad et al, 2017 ); improved healing from liver injury related to acute on chronic hepatitis ( Shi et al, 2012 ; Lin et al, 2017 ) and ischemic biliary lesions following liver transplantation ( Zhang et al, 2017 ); improved hematopoietic recovery ( Xiao et al, 2013 ; Zhang et al, 2013 ; Xiong et al, 2014 ); and accelerated wound healing ( Falanga et al, 2007 ). From these indications, remestemcel-L is already in phase III trials for advanced heart failure and chronic low back pain.…”
Section: Infusion Of Mscs For Tissue Repair and Regenerationmentioning
confidence: 99%